Images of Distortions in the Urban Space. The Example of Lodz - Tobiasz-Lis, Paulina; Wójcik, Marcin (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The city of Lodz was developing from the beginning of the 19th century as a center of textile industry in Eastern Europe. Because of industrial past socio-economical distortions were characteristic for the city of Lodz and still play a crucial role in its urban landscape. The purpose of this paper is to present and interpret existing distortions in the city of Lodz through individual experience, using photography as a research method. Photographic essays prepared by 75 students of geography at the University of Lodz in spring of 2011 and 2012, present a subjective image of Lodz, on the basis of which one can draw conclusions about the social interpretation and evaluation of both the city and its parts. It seems that this type of studies showing an emotional relationship to the urban space may be important for the strategy and planning of local development, pointing out problem areas that require conservation, restoration, or deeper functional and spatial transformations.